A Post-occupancy Evaluation of a Modular Multi-residential Development in Melbourne, Australia. (2017) - Woo, Jin
Abstract: Modular construction has been promoted to minimise the environmental impacts such as construction material use and waste, embodied energy and carbon emissions as well as construction time and cost reduction. Although the main focus has been on the construction technology, waste minimisation, energy and material efficiency and thermal performance of modular construction, limited attention has been paid to the building occupants. This paper aims to evaluate the resident lived experience of a modular multi-residential development in inner Melbourne. The case study building accommodates a total of 199 apartments and commercial spaces, and to date, it is the largest modular construction building in Victoria. A post-occupancy evaluation (POE) was conducted using the Building Use Survey (BUS) methodology. Overall building design, thermal comfort, noise, lighting and personal control over the indoor environment were evaluated on a seven-point Semantic differential scale. Although the building occupant survey showed a high level of satisfaction with overall building design and performance, two main issues, 'thermal discomfort in summer' and 'noise from outside' were identified. Overheating in summer is not clearly understood in this study, however, it could be interpreted that passive design strategies such as cross ventilation and landscaped shared open space increased noise. A further research on the effects of building design on occupants such as engineered light-weight concrete floor, prefabricated building façade, cross-ventilation, operable openings and the cooling systems of the individual apartments is necessary to resolve the issues and to examine whether the poor thermal performance in summer could be related to modular construction. This case study building was developed as a commercially replicable pilot, providing affordable and sustainable high-density housing in Melbourne's inner suburbs. Thus, it is expected that this POE study could provide an insight into the interaction between the building and its occupants, particularly in the context of modular construction, and further contribute to developing high-performance modular multi-residential buildings.